Second step modifications of epoxidised polymers. 5. Systems allowing release of naphtyhlacetic acid from epoxidised polyisoprene and liquid natural rubber - Soutif Jean-Claude; Brosse; Klimituksa Pairote (Journal of Natural Rubber Research, 1993)
A polymeric support containing free or linked naphthylacetic acid (NAA) a stimulator for the production of latex by Hevea can be obtained from epoxidised synthetic 1,4-polyisoprene or liquid natural rubber (LNR). Crosslinking of emulsified epoxidized polymers containing free or bound NAA by diacids or anhydrides catalysed by the tetrabutylammonium salt of the corresponding diacids leads to polymeric particles containing free NAA. Hydrolysis of NAA derivatives of epoxidised 1,4-polyisoprene and epoxidised LNR has been performed in basic media. This particular formulation leads to a high initial rate of liberation.